Pengembangan Video Cara Transaksi Anjungan Tunai Mandiri (ATM) untuk Pembelajaran Kecakapan Hidup Peserta Didik Tunagrahita - Prameswari, Aloysia Dian Nimas; Masitoh, Siti; Wagino, Wagino (Dinasti Research, 2025)
Students with intellectual disabilities often face challenges in mastering life skills, including the ability to perform basic financial transactions such as checking balances and withdrawing cash. These life skills are crucial for supporting their independence and active participation in daily life. This study aimed to develop an instructional video on Automated Teller Machine (ATM) transactions tailored to the needs of students with intellectual disabilities. The research employed the Research and Development (R&D) method using the ADDIE model, encompassing five stages: analysis, design, development, implementation, and evaluation. Validation was conducted by subject matter and media experts, followed by practicality tests by teachers and effectiveness tests through pretests and posttests with students. The results demonstrated that the developed video met validity criteria, requiring minor revisions in content but no revisions in media design. Practicality tests indicated that the video was highly user-friendly, engaging, and motivating for students. Effectiveness tests using the Wilcoxon Signed Rank Test showed significant improvement in understanding, with a p-value of 0.005. In conclusion, the video was proven valid, practical, and effective in enhancing the life skills of students with intellectual disabilities, particularly in basic financial skills. This video is expected to serve as an innovative solution to help these students achieve greater independence in their daily lives.